Tansformasi Nilai Keislaman Melalui Kitab Lokal Kajian Teks Kitab Niyat Ingsun Ngaji Karya KH. Badawi Hanafi - Aris Hidayat (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
Islamic faith should be taught to communities since early ages. Thisaims for filtering them from the deviate ideology. One of the ways is teachingclassic books. This studies local book entitled Niyat Ingsun Ngaji written byKH.Badawi Hanafi. This uses an intertekstual method with other books suchas Nur al-Zalam written by Syekh Nawawi Al-Bantani, Rawihat al-Aqwamwritten by KH.Bisri Mustafa, and Aqidah al-Awam written by Sayid Ahmadal-Marzuqi. Content of the book is analyzed using critical discourse analysis.It is to know transformation of value, interpretation, and response of kyaiand santri. Finding of the research illustrates that Islamic transformationis limited in knowledge transformation. There is difference explanation ofGod’s character and Prophet’s character given by KH.Badawi Hanafi, SyekhNawawi al-Bantani and KH.Bisri Mustafa. Interpretation of kyai and santritoward content of the book Niyat Ingsun Ngaji is relatively the same as thepredecessor. Their response is more likely an introspective meaning whichtends to enhance inner faith.Keywords: classic book, transformation, Faith, interpretation, respond